Strong Metal-Support Interaction in Pt/TiO sub(2) Induced by Mild HCHO and NaBH sub(4) Solution Reduction and Its Effect on Catalytic Toluene Combustion - Rui, Zebao; Chen, Lingye; Chen, Huayao; Ji, Hongbing (Industrial & engineering chemistry research, 2014)
Strong metal-support interaction (SMSI) in titania supported noble metals has been a subject of many studies due to its importance to many fields of science, in particular to material science and catalysis system. H sub(2) reduction at a high temperature has been commonly considered as the inducement to SMSI in TiO sub(2) supported noble metals. This work, however, demonstrates that SMSI in Pt/TiO sub(2) can occur through mild NaBH sub(4) and HCHO solution reduction processes based on CO chemisorption, transmission electron microscopy, and X-ray photoelectron spectroscopy characterizations. Moreover, the effect of TiO sub(2) crystalline forms on the degree of SMSI in NaBH sub(4) reduced Pt/TiO sub(2) and the performance of the as-reduced catalysts for trace toluene combustion reaction were studied. It was found that the degree of SMSI in Pt/TiO sub(2) drew a significant effect on the catalytic performance. Our discovery provides a new way to control the interaction between noble metals and the TiO sub(2) support as well as their catalytic activities.